Гендерная идентичность и конструирование памяти кризисных моментов истории: женские стратегии выживания - Суковатая, В. (Iнститут соціології НАН України, 2009)
The article is devoted to the analysis of the Ukrainian women's autobiographical narratives, whose youth has concurred with the war and post-war periods of the Soviet history. The methodology of research is based on principles of gender theory, oral history and the philosophy of everyday life. The qualitative methods of the analysis of interview are used by the author. The purpose of research is: reconstruction of the sources of women's identity forming in the Soviet (Stalinist) period, the ways of their sexual individualization under conditions of the totalitarian authority, correlation of personal and public events in the women's memory of the senior generation. The result of research is: description of different strategies of the women's individualities' adaptation to the requirements of the totalitarian authority, which can be defined as: a "protest type" (critical in relation to official values), a "romantic femininity" (adapting to official gender requirements), "a flirting with the authority" (aspiring to become a "part" of totalitarian authority). Each of these strategies assumes a physical survival in conditions of totalitarian culture by breaking, or, on the contrary, preservation of individual system of moral values.